Sistem Informasi Pemasaran Kerupuk Ganepo Menggunakan E-Commerce Berbasis Web - Cahya Ferdiansya; Sri Handayani; Kirman Kirman; Monsya Juansen (UNIVED Press, 2024)
The development of technology and information has had a significant impact on the business world, especially through the use of the internet as a means of information and communication. E-commerce is a major business trend today, enabling expanded marketing and increased profits for business people. Effective marketing is the key to success in business, with a focus on retaining customers and meeting their expectations. The use of the internet and digital technology has made it possible to sell goods and services online through various platforms, including online shops, social media and websites. Previous research shows that the application of e-commerce in marketing products such as local crafts and snacks has succeeded in increasing competitiveness and sales. Case studies on Small, Micro and Medium Enterprises (MSMEs) also highlight the importance of using web-based media to increase product promotion and sales. In this context, further research was conducted to explore the potential of online marketing for MSME businesses, with a focus on developing a web-based online shop for Ganepo cracker products. It is hoped that the results of this research can contribute to improving the understanding and practice of online marketing for MSME players, as well as expanding the reach and knowledge of their products in the digital market